Given the roots of a quadratic equation:
![(2\pm i√(3))/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/ppcbxq743wcs11vbyetuawjdkbcoxif0vh.png)
Let's find the equation in standard form.
Apply the standard form of a quadratic equation:
![ax^2+bx+c=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/mvkhuzwnjhb4epaf7jjcoq2vi4zdi4350m.png)
Now, we have:
![(x-(2+i√(3))/(2))(x-(2-i√(3))/(2))=0](https://img.qammunity.org/2023/formulas/mathematics/college/qtfmjxem1iupljgwv4cml9kgw8wkqg0yt2.png)
Now, let's expand the equation.
We have:
![\begin{gathered} x(x-(2-i√(3))/(2))-(2+i√(3))/(2)(x-(2-i√(3))/(2))=0 \\ \\ (x^2*2-x(2-i√(3))-x(2-i√(3)))/(2)+(7)/(4)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/sqx4dsjuewj48q783ky5swknokufroz44b.png)
Solving further:
![\begin{gathered} (x(2x-2+√(3)i-(2+√(3)i)))/(2)+(7)/(4)=0 \\ \\ (x(2x-4))/(2)+(7)/(4)=0 \\ \\ x(x-2)+(7)/(4)=0 \\ \\ x^2-2x+(7)/(4)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/eifr8d8lb316v27yixefaz3mr17t90pv6g.png)
Therefore, the equation in standard form is:
![x^2-2x+(7)/(4)=0](https://img.qammunity.org/2023/formulas/mathematics/college/vliuvb0ol9dou86kwymh0vbs63rw70bzxl.png)
ANSWER:
![x^(2)-2x+(7)/(4)=0](https://img.qammunity.org/2023/formulas/mathematics/college/mkne7b3q77e3rqnkvvyetjnpyc2pzyl6e0.png)